IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 18/PUU-XVII/2019 TERHADAP PELAKSANAAN PERJANJIAN YANG BEROBJEK JAMINAN - Hasani, Jazau Elvi; Trianingsih, Fitri Agustina; Rizky Saraswati, Nadiya Ayu (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2020)
Abstract A fiduciary guarantee is a law product that is applied to protect creditors in particular. When the debtor defaults, the creditor can request compensation from the debtor through execution of a fiduciary guarantee. The Constitutional Court (MK) issued Decision Number 18 / PUU-XVII / 2019 related to the application for judicial review of Law Number 42 of 1999 concerning Fiduciary Guarantees Article 15 paragraph 2 and Article 15 paragraph 3 of the 1945 Republic of Indonesia Constitution. The Constitutional Court granted the petitioners part of the petition, stating Article 15 paragraph (2), Article 15 paragraph (3), and Elucidation of Article 15 paragraph (2) of Law Number 42 the Year 1999 concerning Fiduciary Security contradicts the 1945 Constitution and has no legal force binding. Application related to the implementation of Article 15 paragraph (2) and paragraph (3) of Law No. 42/1999 concerning Fiduciary Guarantee which subsequently reads following Article 15 paragraph (2)